2004
DOI: 10.1016/j.ehj.2004.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic manipulation in ischaemic heart disease, a novel approach to treatment

Abstract: Antianginal drugs that exert their anti-ischaemic effects primarily by altering myocardial metabolism have recently attracted attention. They have the potential to relieve symptoms in patients with refractory angina who are already on "optimal" medical therapy and have disease that is not amenable to revascularisation, making these drugs an attractive addition to therapy, particularly for the elderly population. In some cases, they may even be used as first-line treatment. These drugs increase glucose metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
131
0
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(143 citation statements)
references
References 59 publications
2
131
0
10
Order By: Relevance
“…Nanoburrs technique has also been utilized by the researchers to combat cardiovascular diseases. These are the nanoparticles covered with an adhesive protein that makes them adhere to arterial walls while they gradually discharge medications [37].…”
Section: Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Nanoburrs technique has also been utilized by the researchers to combat cardiovascular diseases. These are the nanoparticles covered with an adhesive protein that makes them adhere to arterial walls while they gradually discharge medications [37].…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Number of studies have been reported in past few years related to the efficacy and safety of various nanoparticles like cholesteroltethered platinum II-based supramolecular nanoparticle [37][38][39][40][41], polymeric-ceramic nanocarriers (NCs) in order to achieve oral delivery of the anticancer neutraceutical iron-saturated bovine lactoferrin (Fe-bLf) protein) [42,43], novel alginate-enclosed chitosan-calcium phosphate-loaded iron-saturated bovine lactoferrin nanocarriers for oral delivery in colon cancer therapy etc. [44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Возни-кающее при этом уменьшение количества вырабатывае-мой митохондриями энергии не способствует образова-нию соединений, богатых макроэргическими связями, что приводит к истощению энергетических ресурсов кардиомиоцитов. Описанные функциональные наруше-ния проявляются структурными изменениями морфоло-гии митохондрий: отмечается их набухание и последую-щее сморщивание (при метаболическом ацидозе), уменьшение в размерах; изменяется проницаемость их мембран, приводящая к неминуемому разрушению орга-неллы; исчезают кристы, на которых проходит процесс окислительного фосфорилирования; появляются ка-пельные жировые включения [2]. Примерная схема по-следовательности метаболических нарушений при ише-мии миокарда представлена на рис.…”
Section: патогенетические аспекты метаболических нарушенийunclassified
“…Etomoxir {2-[6-(4-chlorophenoxy)hexyl]oxirane-2-carboxylate} is an irreversible inhibitor of carnitine palmitoyl transferase I (CPT-I) that was initially introduced as a potential antidiabetic agent based on its hypoglycemic effects (Lee et al, 2004, Lopaschuk et al 2010). …”
Section: Structure Of Etomoxirmentioning
confidence: 99%